Risk of serious infection in healthcare workers with inflammatory bowel disease: a case‐control study of the Groupe d'Etude Thérapeutique des Affections Inflammatoires du tube Digestif (GETAID). Issue 7 (2nd August 2018) - Gagnière, Charlotte; Bourrier, Anne; Seksik, Philippe; Gornet, Jean‐Marc; DeWit, Olivier; Nancey, Stephane; Altwegg, Romain; Abitbol, Vered; Laharie, David; Reenaers, Catherine; Buisson, Anthony; Pariente, Benjamin; et al.
Summary: Background: Whether healthcare workers with inflammatory bowel disease (IBD) are at increased risk of severe infection due to daily pathogen exposure is controversial. Aim: To assess the risk of severe infection in healthcare workers with IBD in a large multicentre case‐control study. Methods: The study population comprised 482 healthcare workers with IBD from 17 centres who were matched for gender, age, disease subtype and year of diagnosis to 482 controls (non‐healthcare workers with IBD). The study period was between the date of diagnosis of IBD and June 2016. Severe infection was defined as any community‐acquired infection that required hospitalisation. Results: With a median follow‐up of 9.3 years, 139 severe infections were recorded among cases and controls, including 30 Clostridium difficile infections, 33 severe viral infections, nine tuberculosis infections, 21 community‐acquired pneumonia and 46 others. No difference was observed between healthcare workers and controls regarding the overall incidence rates of severe infection. An increased risk of tuberculosis was noted in healthcare workers. In multivariate analysis in the entire study population, severe infection was associated with current exposure to corticosteroids (OR = 3.05, 95% CI [2.06‐4.52], P < 0.001), immunosuppressants (OR = 1.98, 95% CI [1.38‐2.84], P < 0.001) and anti‐TNF agents (OR = 2.93, 95% CI [2.02‐4.27], P < 0.001) and reduced with Crohn's disease (OR = 0.63, 95% CI [0.43‐0.91], P = 0.01). Conclusions: Healthcare workers with IBD do not have an increased risk of severe infection compared with other patients with IBD, except for tuberculosis. Screening for tuberculosis exposure should be assessed in this high‐risk population when treated with anti‐TNF agents.